Parental involvement in storybook reading in English project: beyond the reading vocabulary - Madhubala Bava Harji,; Kavitha Balakrishnan, (Penerbit Universiti Kebangsaan Malaysia, 2019)
Since the 60s, research on emergent literacy has presented empirical evidence for the links between storybook reading to young children, parental involvement and language development. Stories, which provide children with vast opportunities to hear new words in a meaningful context subsequently lead to the acquisition of a richer mental model of both the world and vocabulary. Albeit research findings point to the strong causal links between storybook reading, literacy and language, development and parental involvement, little effort appears to be made in Malaysian’s pre-schools to capitalise on storybooks as a vehicle to literacy development and engaging the young children’s first teachers as partners for a common purpose. A structured program that builds bridges between schools and homes is lacking and researched upon. In exploring this missed opportunity, the Smart Partnership in Reading in English (SPIRE) project was piloted in a private preschool. 25 young children, their parents and the class teacher were involved in the project. The mix-mode method was adopted to gather quantitative and qualitative data. Findings show improved reading vocabulary and beyond: receptive and expressive language skills, print awareness, knowledge of grammar, meta-linguistic awareness. Implication is clear; storybooks can be a springboard to develop English literacy skills, specifically reading in English skills. Young learner providers would want to capitalise on this springboard, making learning to read more meaningful and pleasant, and less structured. A serious consideration ought to be made in involving parents (first teachers) to scaffold young learners’ literacy development.